Om bruk av digitale mapper på to grunnskoler - Hvordan kan digitale mapper skape produktive læringsprosesser for elever? - Berit Bratholm (Universitetsforlaget, 2015)
The subject of this article is our experience of working with digital portfolios in primary and lower secondary school. An important theoretical reference for this work has been Engle & Conant's article about how productive academic engagement can be fostered by suitable learning conditions. The project is based on -ethnographic methods. I present different factors which are important for successful interplay between teacher and pupils when working with digital portfolios.